ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN (Studi Pada Bank Umum Go Public yang Listed di Bursa Efek Indonesia Tahun 2011-2013) - Adriel Antonia, Steven; Denny Arfianto, Erman (Faculty of Economics and Business Diponegoro University, 2015)
Bank is a financial institution that aims to make a profit. The profits derived from the management of public funds. Return on Assets (ROA) is one way of measuring the level of the bank's ability to earn a profit. The purpose of this study was to test the return on assets (ROA) which influenced the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), the Loan to Deposit Ratio (LDR), and ROA at commercial banks registered The Indonesia Stock Exchange during 2011-2013.For sampling used purposive sampling method. Data obtained by the publication of the Annual Bank, obtained the number of samples 20 commercial banks to go public. This study used a sample of commercial banks is consistently listed in the Indonesia Stock Exchange during the period 2011-2013. The analysis technique used is multiple linear regression analysis.The results of this study found that the net interest margin (NIM) and ROA has a positive and significant impact on the return on assets (ROA), Capital Adequacy Ratio (CAR) and the loan to deposit ratio (LDR) had no significant positive effect on return on assets (ROA), Non Performing Loan (NPL) has no significant negative effect on the return on assets (ROA).